Socioeconomic Study on the Swimming Crab Rebuilding Plan in Korea - Lee, Sang-Go (Journal of Experimental Sciences, 2010)
Since the establishment and enforcement of the swimming crab stock rebuilding plan in 2006, stock research and evaluation are continuously being conducted on the stock and diverse rebuilding measures are also being considered. The current swimming crab stock rebuilding plan emphasizes policies to reduce fishing pressure and create resources, but it is relatively indifferent about the management of habitats and spawning grounds, protection of marine environment and reduction of pollution. More active participation by fishers and better understanding between fishers groups are required for the effective enforcement of the rebuilding plan, including the TAC policy. Education and information campaigns directed at fishers should be reinforced to support the rebuilding plan as these plans must include broader participation by fishers. Summarizing the results of socioeconomic study on the swimming crab stock rebuilding plan, due to the improvements in the stock status, the swimming crab catch has also increased from 2,683 tonnes(M/T) in 2004 to 17 596 M/T in 2008. The increase is believed to be the result of a combination of rebuilding efforts e.g. clean-up of fishing grounds, release of juvenile crab, stricter enforcement of regulations, and favourable ocean environment, especially high sea surface temperature. As part of the efforts to enhance the environment of the fishing ground, sunken fishing gears, mostly drift nets, were removed by the government. In 2007 alone, 628 M/T of nets were taken out from Yeonpyeng Island area and the Specific Area. In addition, the release of juvenile crab was also undertaken as part of stock enhancement program; 909 000 juvenile crabs were released in 2006-2007. Another important aspect of implementing swimming crab rebuilding plan along with nationwide community-based fisheries management is the increased awareness of fishers regarding the issue, and an increased consensus towards rebuilding.Â Accordingly, the effect of rebuilding plans for sandfish on other related fisheries must sufficiently be taken into consideration. In order to rebuild swimming crab fisheries, a rebuilding plan for the ecosystem must gradually be established and related multi-fisheries should be managed systematically. Â <div style="border-right: medium none; padding-right: 0in; border-top: medium none; padding-left: 0in; padding-bottom: 1pt; border-left: medium none; padding-top: 0in; border-bottom: windowtext 1pt solid; mso-element: para-border-div; mso-border-bottom-alt: solid windowtext .5pt;"> Keywords: Swimming crab rebuilding plan, Socioeconomic study, Swimming crab stock recovers, Fishing mortality, Effects of stock rebuilding plan <div style="border-right: medium none; padding-right: 0in; border-top: medium none; padding-left: 0in; padding-bottom: 1pt; border-left: medium none; padding-top: 0in; border-bottom: windowtext 1pt solid; mso-element: para-border-div; mso-border-bottom-alt: solid windowtext .5pt;"> Dept. of Marine Business & Economics, Pukyong National University, Busan 608-737 Korea Â Â Please Cite This Article As: Sang-Go Lee. 2010. Socioeconomic Study on the Swimming Crab Rebuilding Plan in Korea. J. Exp. Sci. 1(3): 3-8.